Simultaneous Determination of Twenty-Two Components in Asari Radix et Rhizoma by Ultra Performance Liquid Chromatography Coupled with Quadrupole Time-of-Flight Mass Spectrometry - Wen, Hao; Gao, Hui-yuan; Qi, Wen; Xiao, Feng; Wang, Li-li; Wang, Dong; Yuan, Dan (Planta Medica, 2014)
Asari Radix et Rhizoma is a herbal medicine for the treatment of common cold, rhinitis, etc. An ultra performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry method has been established for the rapid analysis of 22 components in 27 samples from the raw materials of Asari Radix et Rhizoma and an adulterant. A total of 5 lignans, 5 essential oils, 3 aristolochic acids, 4 alkamides, and 5 flavanoids were identified by co-chromatography of samples extracts and comparison of the retention time, UV spectra, characteristic molecular ions, and fragment ions with those of authentic standards, or tentatively identified by MS/MS determination along with MassFragment software. Moreover, the method was validated for the simultaneous quantification and semi-quantification of 20 components. The samples from Asarum heterotropoides var. mandshuricum differed in the quantity of 2-methoxyl-4,5-methylenedioxypropiophenone and kakuol from those of Asarum sieboldii var. seoulense, and the chemical difference was supported by principal component analysis and orthogonal partial least squared discriminant analysis based on dataset obtained from UHPLC-QTOF/MS. In comparison with the samples from the two medicinal Asarum species mentioned above, those from A. himalaicum differed in the quality and quantity of major compounds and contained higher amounts of aristolochic acid I.
Keywords: Asari Radix et Rhizoma; Aristolochiaceae; lignans; essential oils; aristolochic acids; UHPLC-QTOF/MS